Boosting the rate capability of hard carbon with an ether-based electrolyte for sodium ion batteries. Issue 20 (10th May 2017) - Zhu, Yuan-En; Yang, Leping; Zhou, Xianlong; Li, Feng; Wei, Jinping; Zhou, Zhen
Abstract : An ether-based electrolyte was used to reduce polarization and improve the plateau capacity at high rates of loofah sponge-derived hard carbon as the anode material for sodium ion batteries for the first time. The optimization of electrolytes could promote the practical application of hard carbon to sodium ion batteries. Abstract : Hard carbon is considered as the most prospective anode material for sodium ion batteries. However, the loss of plateau capacities at high rates, arising from large electrochemical polarization, causes rapid degradation in the rate performances of batteries. In this work, we found that the plateau capacities of hard carbon at high rates could be significantly enhanced in ether-based electrolytes.